Nrf2 in the Field of Dentistry with Special Attention to NLRP3 - Lisa Schieffer; Claudia Manzl; Christoph Schatz; Johannes Haybaeck; Adriano Crismani (Antioxidants, 2022)
The aim of this review article was to summarize the functional implications of the nuclear factor E2-related factor or nuclear factor (erythroid-derived 2)-like 2 (Nrf2), with special attention to the NACHT (nucleotide-binding oligomerization), LRR (leucine-rich repeat), and PYD (pyrin domain) domains-containing protein 3 (NLRP3) inflammasome in the field of dentistry. NLRP3 plays a crucial role in the progression of inflammatory and adaptive immune responses throughout the body. It is already known that this inflammasome is a key regulator of several systemic diseases. The initiation and activation of NLRP3 starts with the oral microbiome and its association with the pathogenesis and progression of several oral diseases, including periodontitis, periapical periodontitis, and oral squamous cell carcinoma (OSCC). The possible role of the inflammasome in oral disease conditions may involve the aberrant regulation of various response mechanisms, not only in the mouth but in the whole body. Understanding the cellular and molecular biology of the NLRP3 inflammasome and its relationship to Nrf2 is necessary for the rationale when suggesting it as a potential therapeutic target for treatment and prevention of oral inflammatory and immunological disorders. In this review, we highlighted the current knowledge about NLRP3, its likely role in the pathogenesis of various inflammatory oral processes, and its crosstalk with Nrf2, which might offer future possibilities for disease prevention and targeted therapy in the field of dentistry and oral health.